Detection of HCOOH, CH3OH, CO, HCN, and C2H6 in Wildfire Plumes Transported Over Toronto Using Ground‐Based FTIR Measurements From 2002–2018. Issue 16 (24th August 2020) - Yamanouchi, Shoma; Strong, Kimberly; Lutsch, Erik; Jones, Dylan B. A.
Abstract: The Fourier transform infrared (FTIR) spectrometer at the University of Toronto Atmospheric Observatory has been operational since 2002, collecting solar absorption spectra from which atmospheric trace gas profiles and columns are retrieved. The time series of total columns of CH3 OH and HCOOH over Toronto are presented here for the first time, along with those for CO, HCN, and C2 H6 . Transport of wildfire plumes over the site results in enhanced columns of biomass burning species. Here we report the detection of biomass burning enhancement events between 2002 and 2018. Several simultaneous enhancements of CO, HCN, and C2 H6 were observed, and the measured columns were used to derive emission ratios and emission factors for HCN and C2 H6 for fire events in 2012, 2015, and 2017. From these events, which included plumes from both boreal and temperate forest fires, emission ratios with respect to CO were derived using CO lifetimes of 30 and 61 days. HCN emission ratios range between 0.0037 ± 0.0003 and 0.0057 ± 0.0008, while C2 H6 emission ratios vary from 0.00122 ± 0.0015 to 0.019 ± 0.001. Enhanced columns of CH3 OH and HCOOH were also observed during the 2015 and 2017 events, and emission ratios were derived but have greater uncertainties due to shorter lifetimes and other sources for these gases. The FLEXPART, HYSPLIT, and GEOS‐Chem models were used for source attribution and traveltime estimation. GEOS‐Chem was run in the tagged CO simulation mode and successfully captured the CO enhancements from fires for the 2015 and 2017 events. Key Points: The first long‐term time series of HCOOH and CH3 OH columns over Toronto were derived from FTIR solar absorption spectra Time series of HCOOH and CH3 OH show seasonal cycles that are consistent with previous studies, with maxima occurring in summer Wildfire emission factors were derived from enhanced CO, HCN, C2 H6, CH3 OH, and HCOOH, but those for HCOOH and CH3 OH have large uncertainties